Anthropogenic nesting sites allow urban breeding in burrowing parrots Cyanoliseus patagonus - Tella Escobedo, José Luis (2014)
How birds adapt to urban life is a key question in evolutionary and conservation biology since urbanisation is one of the major causes of habitat loss worldwide. Some species are able to deal with these anthropogenic changes but a shortage of nesting sites may preclude them from breeding in cities. We conducted a baseline survey of the cliff-nesting burrowing parrot Cyanoliseus patagonus around Bahía Blanca (Argentina), estimating a minimum total of 1,361 pairs breeding at 24 sites (colonies) in 2013. The species showed facultative colonial behaviour, colony size varying between 1 and 300 pairs. Most colonies (68%) and pairs (74%) occupied human-made substrates, mostly quarries but also water wells. Colony size was strongly correlated to the extent of both natural and anthropogenic nesting substrates, suggesting an ideal free distribution of pairs according to the availability of nesting resources. Anthropogenic substrates have certainly allowed population expansion in what is a rather flat landscape with a shortage of cliffs and ravines, as well as urban breeding by a large part (61%) of the surveyed population. This is currently one of the largest populations of burrowing parrots, a previously abundant species that is progressively threatened by persecution and nest poaching for the international pet trade.